Constitutive RB1 mutation in a child conceived by in vitro fertilization: implications for genetic counseling - Lucena Evandro; Vargas Fernando R; Barbosa Raquel H; Bonvicino Cibele R; Seuánez Héctor N (BMC, 2009)
Abstract Background The purpose of this study was to identify mutations associated with bilateral retinoblastoma in a quadruplet conceived by in vitro fertilization, and to trace the parental origin of mutations in the four quadruplets and their father. Methods Mutational screening was carried out by sequencing. Genotyping was carried out for determining quadruplet zygosity. Results The proband was a carrier of a novel RB1 constitutive mutation (g.2056C>G) which was not detected in her father or her unaffected sisters, and of two other mutations (g.39606 C>T and g.174351T>A) also present in two monozygotic sisters. The novel mutation probably occurred de novo while the others were of likely maternal origin. The novel mutation, affecting the Kozak consensus at the 5'UTR of RB1 and g.174351T>A were likely associated to retinoblastoma in the proband. Conclusion Molecular diagnosis of retinoblastoma requires genotypic data of the family for determining hereditary transmission. In the case of children generated by IVF with oocytes from an anonymous donor which had been stored in a cell repository, this might not be successfully accomplished, making precise diagnosis impracticable for genetic counseling.